Influence of requirements for explosion-proof equipment on its design processes - Rybakov, Vadym (National Technical University "Kharkiv Polytechnic Institute", 2024)
The necessity of analysis the influence of requirements for explosion-proof equipment on the design processes of such equipment caused by the lack of a clear sequence of actions when ensuring explosion protection of equipment. General design tasks (for example, ensuring reliability indicators, product performance characteristics, etc.) and design stages do not take into account the requirements for explosion safety and conformity assessment, which makes it necessary to formulate and research these connections in order to improve the design process of explosion-proof equipment, with subsequent successful passing the assessment of compliance with technical regulations No. 1055.
Keywords: explosion protection; explosion-proof equipment; explosion protection standards; conformity assessment processes; design processes